English Tutoring for Orphanage Children - Kara, Yuliana Maria D’ Karmel; Sama, Gratiana; Wanggai, Febe F Irawati; Nuri, Nur Aida Bhara (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
This Community Service (CS) activity has the theme of introducing English learning for children at Naungan Kasih Orphanage of St. Elisabeth Ende. This is done with the aim of guiding children in this Orphanage so that they can have English skills and knowledge. The main problem faced by these children is for kindergarten and elementary school children, are not yet familiar with English, while high school level children already know and obtain English learning, but with limited media, time, etc. so they learn less English. This makes them have no motivation and no interest in learning English. This activity went well and they are enthusiastic. This activity uses several learning strategies made by the CS team so that children do not get bored learning English, and have the attraction of learning English. It is expected that the children in this orphanage are able to apply the use of English in schools and communities and overcome the difficulties that they face. Children learn well, full of enthusiasm and it is expected that there will be an improvement in their English learning.